Writing B2 - White, Genevieve (Tổng hợp, 2014)
My image of the 'writing' section in a typical ELT library would be a short, rather dusty, neglected shelf with just a few titles related to either academic writing, exam preparation or perhaps business English. What feels original about this new writing book from Collins is that it contains a wide range of genres with a great variety of personal or work-related writing dealing with different levels of formality and types of audience